Partial Clipping Occlusion Including Rupture Point Is an Effective Strategy for Ruptured Giant Fusiform Basilar Artery Aneurysm: A Technical Case Report - Izumo, Tsuyoshi; Fujimoto, Takashi; Morofuji, Yoichi; Tateishi, Yohei; Matsuo, Takayuki (Frontiers in Neurology, 2021)
Treatment of fusiform basilar artery aneurysms is still challenging today. The authors present a case of a patient with a ruptured giant fusiform basilar artery aneurysm successfully treated by clipping occlusion of the rupture point. A 62-year-old man suddenly fell into a coma due to subarachnoid hemorrhage (SAH) with a ruptured giant fusiform basilar artery aneurysm with a bleb on the right shoulder. We considered treating the lesion with stent-assisted coil embolization because of the aneurysm's shape, but we had to give up because stents were off-label in the acute phase SAH in our country. Instead, we successfully performed clipping surgery to partially occlude the aneurysm, including the rupture point via the anterior transpetrosal approach. His postoperative course was uneventful, without rerupture of the aneurysm, and his conscious level tended to improve. The postoperative imaging studies showed no complications and disappearance of the rupture point of the aneurysm. Although direct surgery for the giant fusiform basilar artery aneurysms is one of the challenging operations, it is an essential and highly effective treatment as a last resort for complex aneurysms if other treatments are not available.